Alcohol advertising and public health: systems perspectives versus narrow perspectives. Issue 3 (27th October 2016) - Petticrew, M; Shemilt, I; Lorenc, T; Marteau, T M; Melendez-Torres, G J; O'Mara-Eves, A; Stautz, K; Thomas, J
Abstract : Background: Alcohol consumption is influenced by a complex causal system of interconnected psychological, behavioural, social, economic, legal and environmental factors. These factors are shaped by governments (eg, licensing laws and taxation), by consumers (eg, patterns of alcohol consumption drive demand) and by alcohol industry practices, such as advertising. The marketing and advertising of alcoholic products contributes to an 'alcogenic environment' and is a modifiable influence on alcohol consumption and harm. The public health perspective is that there is sufficient evidence that alcohol advertising influences consumption. The alcohol industry disputes this, asserting that advertising only aims to help consumers choose between brands. Methods: We review the evidence from recent systematic reviews, including their theoretical and methodological assumptions, to help understand what conclusions can be drawn about the relationships between alcohol advertising, advertising restrictions and alcohol consumption. Conclusions: A wide evidence base needs to be drawn on to provide a system-level overview of the relationship between alcohol advertising, advertising restrictions and consumption. Advertising aims to influence not just consumption, but also to influence awareness, attitudes and social norms; this is because advertising is a system-level intervention with multiple objectives. Given this, assessments of the effects of advertising restrictions which focus only on sales or consumption are insufficient and may be misleading. For this reason, previous systematic reviews, such as the 2014 Cochrane review on advertising restrictions (Siegfried et al ) contribute important, but incomplete representations of 'the evidence' needed to inform the public health case for policy decisions on alcohol advertising. We conclude that an unintended consequence of narrow, linear framings of complex system-level issues is that they can produce misleading answers. Systems problems require systems perspectives.